2015
DOI: 10.3109/00365521.2015.1107752
|View full text |Cite
|
Sign up to set email alerts
|

Short- and long-term outcomes of endoscopic resection of rectal neuroendocrine tumours: analyses according to the WHO 2010 classification

Abstract: Despite the low curative resection rate, prognosis after endoscopic resection of rectal NETs was excellent. Prospective large-scale, long-term studies are required to determine whether NET G2 and tumours >1 cm should be included in the indication for endoscopic resection and whether tumours with lymphovascular invasion can be followed up without additional surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
31
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 29 publications
3
31
1
1
Order By: Relevance
“…Although this retraction artifact should be accurately histologically distinguished from true lymphatic or vascular invasion, identification of true LVI is not always straightforward on routine hematoxylin and eosin (H&E)-stained slides. Recently, ancillary immunohistochemical staining [D2-40, CD34, CD31, and Elastica van Gieson (EVG)] in addition to H&E histologic examination has been used to evaluate LVI in rectal NETs[31-33]. Through these methods, the high frequency of LVI has been noted in endoscopically resected small rectal NETs[32,33].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this retraction artifact should be accurately histologically distinguished from true lymphatic or vascular invasion, identification of true LVI is not always straightforward on routine hematoxylin and eosin (H&E)-stained slides. Recently, ancillary immunohistochemical staining [D2-40, CD34, CD31, and Elastica van Gieson (EVG)] in addition to H&E histologic examination has been used to evaluate LVI in rectal NETs[31-33]. Through these methods, the high frequency of LVI has been noted in endoscopically resected small rectal NETs[32,33].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, ancillary immunohistochemical staining [D2-40, CD34, CD31, and Elastica van Gieson (EVG)] in addition to H&E histologic examination has been used to evaluate LVI in rectal NETs[31-33]. Through these methods, the high frequency of LVI has been noted in endoscopically resected small rectal NETs[32,33]. However, whether the increased detection rate between H&E and ancillary studies is statistically significant has not been determined.…”
Section: Introductionmentioning
confidence: 99%
“…However, a number of recent studies have reported a higher than expected rate of venous and/or lymphatic invasion (lymphovascular invasion) in GEP-NET samples obtained via endoscopic procedures [46]. In a case series from our own institution, we identified a lymphovascular invasion rate of approximately 30 % for GEP-NETs.…”
Section: Introductionmentioning
confidence: 67%
“…However, recent surveillance data have shown the incidence and prevalence of GEP-NETs to be higher than previously expected, likely due to recent technical advances in endoscopic and imaging examinations [8]. In Japan, the rectum is the most frequent site of GEP-NETs [8], as well as the second most common site in Western countries [4]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation